2021
DOI: 10.3390/cancers13143503
|View full text |Cite
|
Sign up to set email alerts
|

MR Thermometry Accuracy and Prospective Imaging-Based Patient Selection in MR-Guided Hyperthermia Treatment for Locally Advanced Cervical Cancer

Abstract: The efficacy of a hyperthermia treatment depends on the delivery of well-controlled heating; hence, accurate temperature monitoring is essential for ensuring effective treatment. For deep pelvic hyperthermia, there are no comprehensive and systematic reports on MR thermometry. Moreover, data inclusion generally lacks objective selection criteria leading to a high probability of bias when comparing results. Herein, we studied whether imaging-based data inclusion predicts accuracy and could serve as a tool for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 74 publications
(151 reference statements)
1
14
0
Order By: Relevance
“…Several studies have shown that MR thermometry assessment in the pelvic region is challenging. 19,22,62 Our previous study showed that the amount of intestinal gas motion at the start of the treatment was an MR thermometry accuracy predictor and that a higher level of motion caused stronger susceptibility artifacts.Hence, patients with a high intestinal gas motion would not be amendable for reliable MR thermometry acquisition. 22 In the current study, three patient groups were defined according to the level of intestinal gas motion (Jaccard coefficient).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that MR thermometry assessment in the pelvic region is challenging. 19,22,62 Our previous study showed that the amount of intestinal gas motion at the start of the treatment was an MR thermometry accuracy predictor and that a higher level of motion caused stronger susceptibility artifacts.Hence, patients with a high intestinal gas motion would not be amendable for reliable MR thermometry acquisition. 22 In the current study, three patient groups were defined according to the level of intestinal gas motion (Jaccard coefficient).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 8 and Table 4 confirm the relation between MAE from filtered MR thermometry and the Jaccard coefficient since patients with higher Jaccard coefficients have a lower MAE. 22 Even though more motion TA B L E 3 MAE and SDE are expressed by the mean ± standard deviation. These were calculated for three different anatomical locations: V-vagina, R-Rectum, and B-Bladder.…”
Section: Evaluation Between Patient Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional other medical procedures with heat such as HIPEC [ 35 ], HIVEC [ 36 ] or thermoablation [ 24 ] are not part of our review. Moreover, hyperthermia generated by high-frequency radiofrequency waves or with microwaves [ 37 ] with an adequate real-time thermal dose monitoring [ 38 , 39 ] meeting the requirements of the ESHO is also explicitly not part of our review [ 25 30 ].…”
Section: Introductionmentioning
confidence: 99%